2007
DOI: 10.1042/bj20070606
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial uncouplers with an extraordinary dynamic range

Abstract: We have discovered that some weak uncouplers (typified by butylated hydroxytoluene) have a dynamic range of more than 10(6) in vitro: the concentration giving measurable uncoupling is less than one millionth of the concentration causing full uncoupling. They achieve this through a high-affinity interaction with the mitochondrial adenine nucleotide translocase that causes significant but limited uncoupling at extremely low uncoupler concentrations, together with more conventional uncoupling at much higher conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
3
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 38 publications
6
103
3
7
Order By: Relevance
“…3) also points to dependence of its uncoupling efficiency upon accumulation in mitochondria, which presumes the self-limiting mode of action of this protonophore. It has been shown recently that a conjugate of triphenylphosphonium with butylated hydroxytoluene exhibited protonophorous action in mitochondria because of its interaction with adenine nucleotide translocase (17). Our experiments showed that the action of SkQR1 was not mediated by this and several other carriers operating in the inner mitochondrial membrane (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…3) also points to dependence of its uncoupling efficiency upon accumulation in mitochondria, which presumes the self-limiting mode of action of this protonophore. It has been shown recently that a conjugate of triphenylphosphonium with butylated hydroxytoluene exhibited protonophorous action in mitochondria because of its interaction with adenine nucleotide translocase (17). Our experiments showed that the action of SkQR1 was not mediated by this and several other carriers operating in the inner mitochondrial membrane (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…It turned out, however, that the conjugate was substantially less active than the parent DNP. Another conjugate of triphenylphosphonium, with butylated hydroxytoluene, exhibited protonophorous activity within a wide range of concentrations because of its interaction with adenine nucleotide translocase (17). It has recently been shown that mitochondria-targeted antioxidants (SkQ1 and 10-(6Ј-ubiquinonyl) decyltriphenylphosphonium) as well as SkQ1 lacking quinone (dodecyltriphenylphosphonium) exhibit protonophorous action when added together with free fatty acids (7).…”
Section: Transport Of Electrons Along the Mitochondrial Respiratory Cmentioning
confidence: 99%
“…Using pharmacological agents to uncouple all mitochondria throughout the body may be a risky treatment, because it might compromise energy homeostasis in other tissues, such as heart and brain, causing irreversible damage. For uncouplers to work safely, these compounds should cause uncoupling that increases very little as their concentration rises, potentially widening the difference between therapeutic and toxic doses and giving a wide therapeutic window (62). Recently, however, targeted uncoupling showing precise spatial and temporal control of mitochondrial function have been demonstrated, leading to the selective uncoupling of either individual or small groups of them within a cell (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 5, the styraxjaponoside A and B-treated cells showed very weak fluorescence compared to CCCP (Lou et al, 2007), an inhibitor of the cell membrane potential. It was speculated that the membrane defects caused by the compounds resulted in the disruption of the structure of the membrane, and the dye might then be released from the membrane.…”
Section: Action Mechanisms Of Styraxjaponoside a And Bmentioning
confidence: 99%